Towards a polemical ethics between Heidegger and Plato - Fried, Gregory, 1961- (New Heidegger research., 2021)
"Martin Heidegger held Plato responsible for inaugurating the slow slide of the West into nihilism and the apocalyptic crisis of modernity. In this book, Gregory Fried defends Plato against Heidegger's critiques. While taking seriously Heidegger's analysis of human finitude and historicity, Fried argues that Heidegger neglects the transcending ideals that necessarily guide human life as situated in time and place. That neglect results in Heidegger's disastrous politics, unhinged from a practical reason grounded in the philosophical search from a truth that transcends historical contingency. Thinking both with and against Heidegger, Fried shows how Plato's skeptical idealism provides an ethics that captures both the situatedness of finite human existence and the need for transcendent ideals. The result is a novel way of understanding politics and ethical life that Fried calls a polemical ethics, which mediates between finitude and transcendence by engaging in constructive confrontation with both traditions and other persons. The contradiction between the founding ideals of the United States and its actual history of racism and slavery provides an occasion to discuss polemical ethics in practice"--